Adrenaline release evokes hyperpnoea and an increase in ventilatory CO2 sensitivity during hypoglycaemia: a role for the carotid body. (5th May 2016) - Thompson, Emma L.; Ray, Clare J.; Holmes, Andrew P.; Pye, Richard L.; Wyatt, Christopher N.; Coney, Andrew M.; Kumar, Prem
Abstract : Key points: Hypoglycaemia is counteracted by release of hormones and an increase in ventilation and CO2 sensitivity to restore blood glucose levels and prevent a fall in blood pH. The full counter‐regulatory response and an appropriate increase in ventilation is dependent on carotid body stimulation. We show that the hypoglycaemia‐induced increase in ventilation and CO2 sensitivity is abolished by preventing adrenaline release or blocking its receptors. Physiological levels of adrenaline mimicked the effect of hypoglycaemia on ventilation and CO2 sensitivity. These results suggest that adrenaline, rather than low glucose, is an adequate stimulus for the carotid body‐mediated changes in ventilation and CO2 sensitivity during hypoglycaemia to prevent a serious acidosis in poorly controlled diabetes. Abstract: Hypoglycaemia in vivo induces a counter‐regulatory response that involves the release of hormones to restore blood glucose levels. Concomitantly, hypoglycaemia evokes a carotid body‐mediated hyperpnoea that maintains arterial CO2 levels and prevents respiratory acidosis in the face of increased metabolism. It is unclear whether the carotid body is directly stimulated by low glucose or by a counter‐regulatory hormone such as adrenaline. Minute ventilation was recorded during infusion of insulin‐induced hypoglycaemia (8–17 mIU kg −1  min −1 ) in Alfaxan‐anaesthetised male Wistar rats. Hypoglycaemia significantly augmented minute ventilation (123 ± 4 to 143 ± 7 ml min −1 ) and CO2 sensitivity (3.3 ± 0.3 to 4.4 ± 0.4 ml min −1  mmHg −1 ). These effects were abolished by either β‐adrenoreceptor blockade with propranolol or adrenalectomy. In this hypermetabolic, hypoglycaemic state, propranolol stimulated a rise in P aC O 2, suggestive of a ventilation–metabolism mismatch. Infusion of adrenaline (1 μg kg −1  min −1 ) increased minute ventilation (145 ± 4 to 173 ± 5 ml min −1 ) without altering P aC O 2 or pH and enhanced ventilatory CO2 sensitivity (3.4 ± 0.4 to 5.1 ± 0.8 ml min −1  mmHg −1 ). These effects were attenuated by either resection of the carotid sinus nerve or propranolol. Physiological concentrations of adrenaline increased the CO2 sensitivity of freshly dissociated carotid body type I cells in vitro . These findings suggest that adrenaline release can account for the ventilatory hyperpnoea observed during hypoglycaemia by an augmented carotid body and whole body ventilatory CO2 sensitivity. Key points: Hypoglycaemia is counteracted by release of hormones and an increase in ventilation and CO2 sensitivity to restore blood glucose levels and prevent a fall in blood pH. The full counter‐regulatory response and an appropriate increase in ventilation is dependent on carotid body stimulation. We show that the hypoglycaemia‐induced increase in ventilation and CO2 sensitivity is abolished by preventing adrenaline release or blocking its receptors. Physiological levels of adrenaline mimicked the effect of hypoglycaemia on ventilation and CO2 sensitivity. These results suggest that adrenaline, rather than low glucose, is an adequate stimulus for the carotid body‐mediated changes in ventilation and CO2 sensitivity during hypoglycaemia to prevent a serious acidosis in poorly controlled diabetes.